National Education Policy 2020: Paving the Path for Holistic Management Education in India - Kandwal, Naveen Prakash; Negi, Shalini (International Journal of Engineering and Management Research, 2024)
The National Education Policy (NEP) of 2020 signifies a paradigm shift in the landscape of education in India. The NEP 2020 envisages a transformative journey towards a holistic and multidisciplinary educational framework. This research delves into the sub-theme of "Focus on holistic, multidisciplinary learning instead of rote learning" within the context of management education. The research explores the rationale behind this shift, analyzing how the NEP 2020 aligns with the need for holistic education in the field of management. It examines various provisions of the policy to understand the policy's inclination to break away from the conventional rote memorization model. It investigates how holistic learning approach fosters a more comprehensive understanding of management concepts, encouraging management students to connect theoretical knowledge with real-world applications. Furthermore, the research explores the integration of multidisciplinary learning and incorporation of Indian Knowledge System (IKS) within the management curriculum. The NEP 2020 advocates for a flexible and broad-based education system, allowing students to explore diverse subjects and develop a well-rounded skill set. This approach not only enhances the adaptability of future managers but also nurtures a holistic perspective essential for effective leadership in today's dynamic business environment. Through an in-depth analysis of the NEP 2020 provisions and their implications for management education, this research sheds light on the challenges and opportunities presented by the shift from rote learning to holistic, multidisciplinary learning. The findings contribute valuable insights into the ongoing educational reforms in India for educators, policymakers and stakeholders in the management education sector.